SPSS explained - Hinton, Perry R. 1954-; McMurray, Isabella 1970-; Brownlow, Charlotte; Terry, Peter C. 1952- (Routledge, Taylor & Francis Group, 2024)
SPSS Explained provides the student with all that they need to undertake statistical analysis using SPSS. It combines a step-by-step approach to each procedure with easy-to-follow screenshots at each stage of the process. A number of other helpful features are provided, including:- regular advice boxes with tips specific to each test- explanations divided into ‘essential’ and ‘advanced’ sections to suit readers at different levels- frequently asked questions at the end of each chapterThe third edition of this popular book has been fully updated for IBM SPSS version 27 and also includes:- a new chapter on how to undertake mediation and moderation with SPSS- updates on changes to SPSS, including updated functionality within ANOVAs and calculations of a priori power analysisPresented in full colour and with a fresh, reader-friendly layout, this fully updated new edition also comes with online support material featuring an array of supplementary resources for students and instructors.Minimal prior knowledge is assumed, so the book is well designed for the novice user, but it will also be a useful reference source for those developing their own expertise in SPSS. It is suitable for all students who need to do statistical analysis using SPSS in various disciplines, including psychology, social science, business studies, nursing, education, health and sport science, communication and media, geography, and biology.The authors have many years of experience in teaching SPSS to students from a wide range of disciplines. Their understanding of SPSS users’ concerns, as well as a knowledge of the type of questions students ask, form the foundation of this book